Delayed intracerebral hemorrhage associated with placement of a deep brain stimulating electrode over two years prior. (June 2021) - Radziunas, Andrius; Deltuva, Vytenis Pranas; Tamasauskas, Arimantas; Bunevicius, Adomas; Falowski, Steven
Abstract: Introduction and importance: Most severe complications of DBS appear in the perioperative period. There are no published case reports of delayed ICH occurring more than three months from electrode implantation. The pathogenesis of delayed ICH remains unclear. Case presentation: We present a 64-year-old male with essential tremor who sustained a delayed intracerebral hemorrhage (ICH) 2.5 years after implantation of a deep brain stimulating electrode. Discussion: The patient sustained a thalamic-midbrain ICH that may have been related to the positioning of the electrode. An analysis was performed to determine the cause and risk factors that may have contributed. Based on these findings, it is possible that the proximity of the cannula or electrode may have mildly injured the wall of the superior thalamic vein during implantation, or perhaps being in contact with the vein over a longer-term having an effect, which in either of these scenarios can subsequently lead to ICH formation on the sudden rise of intracranial pressure. Conclusion: It emphasizes the importance of proper surgical navigation planning, image- guidance, and the use of image verification. Highlights: No reports of delayed ICH occurring more than 3 months from DBS electrode implantation A delayed intracerebral hemorrhage 2.5 years after implantation of a DBS electrode is reported Possible that the cannula or electrode may have injured the wall of superior thalamic vein during implantation DBS candidates should be instructed about delayed ICH risk